The last hot time - Ford, John M. (New York : Tor, 2000)
Danny Holman leaves the cornfields of Iowa for the bright lights of the City, not expecting how drastically his life will change.
"A Tom Doherty Associates book.".
Kirkus Starred.
Library Journal.
Pub Weekly.
Adult
Keywords: Criminals -- Fiction; Elves -- Fiction; Emergency medical technicians -- Fiction; Criminals -- Fiction; Elves -- Fiction; Emergency medical technicians -- Fiction; Chicago (Ill.) -- Fiction; Chicago (Ill.) -- Fiction; Fantastic fiction